Hubungan Antara Regulasi Diri Dengan Student Well-Being Pada Siswa di SMKN X Kota Bekasi - Nuraini, Vivi Meida; Fitriani, Yulia; Pertiwi, Yuarini Wahyu (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study aims to determine the relationship between self-regulation and student well-being at SMKN X Bekasi Citu. Using quantitative methods and a sample of 111 grade XI students. This study found that there was a significant positive relationship between self-regulation and student well-being. The correlation results showed that there was a relationship between self-regulation and student well-being and had a significant positive correlation. The results of the normality test showed that data was distributed normally, so the Alternative Hypothesis (Ha) was accepted.  Thus, it can be concluded that self-regulation has a significant relationship with student well-being in grade XI students at SMKN X Bekasi City.